Enhancing the learning environment in Kunming kindergartens - a comprehensive review of plant landscape design strategies aligned with curriculum standards - Lulu, Ma; S. Muthuveeran, Adam Aruldewan; Na, Dai; Abd Ghafar, Azmiah; Yuxuan, Gao; Yali, Ma (Human Resource Management Academic Research Society, 2023)
This research aims to integrate kindergarten botanical landscape design with the Chinese kindergarten education curriculum, aiming to enhance the learning environment for Chinese children. Through a literature review, this study examines the educational areas that Chinese children need to be exposed to within the kindergarten education framework and the current application status of botanical landscapes in kindergartens. This helps establish an approach for incorporating kindergarten landscape design into early childhood education. The outcomes of this research will contribute to understanding the current application status of botanical landscapes in kindergartens, theories related to Chinese kindergarten curriculum development, and theories regarding the integration of the kindergarten curriculum and botanical configuration. Furthermore, it will propose suitable botanical landscape design strategies aligned with kindergarten curriculum education. This study contributes to the enhanced utilization of botanical landscapes in early childhood education settings, thereby improving the learning environment for Chinese children.